Congenital Self-Healing Langerhans Cell Histiocytosis: A Rare Presentation of Blueberry Muffin Baby "Spectrum" - Katharina Hansel; Marta Tramontana; Stefania Troiani; Diletta de Benedictis; Leonardo Bianchi; Rosa Cucchia; Stefano Simonetti; Luca Stingeni (MDPI AG, 2019)
A case of congenital self-healing Langerhans cell histiocytosis (CSHLCH), also known as Hashimoto-Pritzker disease, is reported. The newborn presented as blueberry muffin baby at birth, showing numerous non-blanching blue-purplish and dark-red papular, nodular lesions without documented infections and systemic involvement. Histopathological and immunohistochemical findings were suggestive for Langerhans cell histiocytosis. During the first 12 weeks of life, the cutaneous lesions progressively and spontaneously regressed with some atrophic scars. One-year follow-up is negative for relapse of cutaneous lesions or systemic involvement, confirming the diagnosis of CSHLCH.